Effectiveness of self-directed virtual learning on retention of cardiopulmonary resuscitation knowledge and skills among hospital nurses in North-Western Nigeria: protocol paper - Saidu, Ahmed; Lee, Khuan; Ismail, Iskasymar; Oyedunni, Arulogun Sola; Lim, Poh Ying (Universiti Putra Malaysia Press, 2023)
Introduction: The instructor-led CPR training method has been used for over 4 decades. However, nurses’ knowledge and skills are still low. Instructor-led CPR training is an extremely capital-intensive programme that requires more time, workforce, and space, thus serving as an impediment to effective learning among the prospective nurses’ trainees. Self-directed training method is suggested to improve the knowledge and skills of CPR among healthcare practitioners due to the low cost and flexibility. This study aims to evaluate the effectiveness of self-directed method in improving nurses’ knowledge and skill retention from baseline to post-test, one, three-, and six months. Method: A two-arm double-blinded randomised controlled trial will be conducted in two referral hospitals. The control group training consists of a one-day session taught by AHA-certified instructors, whereas the intervention group training entails participants learning on computers in a simulation lab for seven days. A generalised estimated equation model will be used for statistical analysis. Discussion: Through the self-directed training method, participants will have significantly better knowledge and skills of CPR compared to the conversational training method across the time points. Self-directed training method is a simple, cost-effective and flexible method, which can facilitate the training of more nurses in the acquisition and retention of knowledge and skills, especially for those who prefer to learn at their own pace.